Pengembangan Media Pembelajaran Matematika Berbasis Aplikasi Android Pada Materi Bentuk Aljabar Untuk Meningkatkan Hasil Belajar Siswa SMP - Maria Operati Edy Jebatu; Juliana M. H. Nenohai; Damianus D. Samo (Universitas Nusa Cendana, 2022)
Technology in education demands innovative and creative learning by utilizing android smartphones to improve student learning outcomes. Therefore, this study aims to develop and produce an android-based application on algebraic form material to improve student learning outcomes for grade VII students of SMP Negeri 8 Kupang that is valid, practical, and effective and to find out teacher and student responses to the application.The method used in this study is the Research and Development (R&D) research method and the model used for ADDIE development which consists of 5 stages, namely analysis, design, development, implementation andevaluation (evaluation). Data collection techniques used are interviews, questionnaires and learning outcomes tests. The data analysis technique used is qualitative data analysis and quantitative data analysis.The results showed that the Algebra Learning Application met the valid, practical and effective eligibility criteria and was able to improve student learning outcomes. The average total validity by material experts is 4.01, education practitioners are 4.23, and media experts are 4.66, with the